Metacognition and cognitive control: behavioural adaptation requires conflict experience. Issue 2 (February 2018) - Questienne, Laurence; Van Opstal, Filip; van Dijck, Jean-Philippe; Gevers, Wim
Cognitive control allows adapting our behaviour to improve performance. A behavioural signature of cognitive control is the Gratton effect. This effect is observed in conflict tasks and indicates smaller congruency effects after incongruent trials than after congruent trials. Metacognitive experience may play a role in this effect: When participants introspect on their conflict experience, the Gratton effect follows the conflict introspection instead of the stimulus congruency. However this Gratton effect could also be triggered by the labelling that the introspective method implies and/or by a misperception of the stimulus conflict. The current study investigated whether the experiential component of the introspection is necessary to trigger cognitive control or whether labelling a trial as conflicting or not can be sufficient. In a priming task, Gratton effects following metacognitive conflict experience and conflict label were contrasted. Replicating earlier reports, results showed that the metacognitive experience of conflict can trigger a Gratton effect. However a conflict label, either generated by the participants themselves or presented to the participants via feedback was not able to induce cognitive control. Results are discussed in light of current theories of cognitive control.